Berastagi Flower Center Dengan Pendekatan Arsitektur Neo-Vernakular - Agryvania Br Sembiring; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Berastagi, Karo Regency is one of the tourist areas in North Sumatra Province as the largest producer of fruit and flowers in North Sumatra. Some flowers that grow in Berastagi such as Chrysanthemum, Sedap Malam, Mawar, Gerberra make a dominant contribution to the total flower production in North Sumatra. Berastagi needs a place that becomes the center for accommodating commercial, educational and recreational activities for the community that can fulfill the needs of flowers, flower cultivation, and flower arrangement services. The method used in this design uses Neo-Vernacular Architecture approach by applying the principles and architectural elements that exist in the Batak Karo traditional house by adding modern elements in, expected to produce a form of appearance of the building in a new form but still maintain the existence of local culture. The concept used is the transformation of the concept Harmony in Diversity, which is expected to display different types of flowers that are tidy and harmonious for commercial, recreational and educational functions that are adapted to the karo traditional buildings that have different functions in one village with family among the communities interwoven harmoniously .Keyword: Neo-Vernacular Architecture, Berastagi, Batak Karo, Flower